2021
DOI: 10.1021/acsestwater.0c00316
|View full text |Cite
|
Sign up to set email alerts
|

An Oxic–Hydrolytic–Oxic Process at the Nexus of Sludge Spatial Segmentation, Microbial Functionality, and Pollutants Removal in the Treatment of Coking Wastewater

Abstract: Toxic inhibition and wash-out of nitrifying bacteria in traditional single-activated sludge processes frequently cause instability of nitrification in industrial wastewater treatment and limit the total nitrogen (TN) removal efficiency. A novel oxic–hydrolytic–oxic (O/H/O) process based on a three-sludge regime was developed to treat coking wastewater with a high C/N ratio and biological toxicity. The results demonstrated that high COD removal (89.6%, 91.3%, 90.4%, and 87.1% in four different modes) was achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Our group has studied coking wastewater treatment technology for over 20 years, and we have designed and operated many coking wastewater treatment projects. Our team has been investigating coking wastewater from 26 projects and found that the COD of coking raw wastewater is 3000–5000 mg/L. ,, The raw wastewater enters the regulation reservoir, and then, the effluent from the regulation reservoir (biological inflow) enters the biological treatment process. The biological influent wastewater quality used for the calibration of TCW-ASM3 model parameters is shown in Table .…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our group has studied coking wastewater treatment technology for over 20 years, and we have designed and operated many coking wastewater treatment projects. Our team has been investigating coking wastewater from 26 projects and found that the COD of coking raw wastewater is 3000–5000 mg/L. ,, The raw wastewater enters the regulation reservoir, and then, the effluent from the regulation reservoir (biological inflow) enters the biological treatment process. The biological influent wastewater quality used for the calibration of TCW-ASM3 model parameters is shown in Table .…”
Section: Methodsmentioning
confidence: 99%
“…Direct anaerobic/anoxic treatment was shown to be inefficient for the treatment of coking wastewater with toxic pollutants. , For toxic wastewater, the aerobic reactor should be placed forward due to the strong resistance of aerobic sludge to OLR and toxicity. Wei et al have showed that the O/H/O process is the most cost-effective process for coking wastewater treatment and has the potential to be extended to the treatment of other wastewaters with similar characteristics . The O/H/O process used biological fluidized bed reactors to form a three-sludge system, which ensures the stability of microbial population structure and process operation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations